Transmission System for a baja vehicle SAE BRASIL (International Journal of Geoscience, Engineering and Technology, 2020)
SAE BRASIL is a program that holds contests where students are encouraged to apply and develop their knowledge in the engineering area. One of its modalities is the baja, which consists of a kind of all-terrain vehicle. In order to improve performance in these competitions, and obtain trophies, this work aims to assemble a transmission system that better adheres to the prototype in a competitive way, guaranteeing the vehicle a good tractive capacity, and a good maximum speed, thus surpassing the old prototype BE-O8, this taking into account the financial and bureaucratic conditions. This system is basically composed of a 19 briggs & stratton series engine, CVT (continuously variable transmission), a pair of CVs, and a transfer box, which when together are also called the power train. Thus, based on the methodology and analysis of the data, it was possible to develop a vehicle better than BE-08 reaching the design premise.